If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4 + -1x) = -3(2 + -1x) (4 * 3 + -1x * 3) = -3(2 + -1x) (12 + -3x) = -3(2 + -1x) 12 + -3x = (2 * -3 + -1x * -3) 12 + -3x = (-6 + 3x) Solving 12 + -3x = -6 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 12 + -3x + -3x = -6 + 3x + -3x Combine like terms: -3x + -3x = -6x 12 + -6x = -6 + 3x + -3x Combine like terms: 3x + -3x = 0 12 + -6x = -6 + 0 12 + -6x = -6 Add '-12' to each side of the equation. 12 + -12 + -6x = -6 + -12 Combine like terms: 12 + -12 = 0 0 + -6x = -6 + -12 -6x = -6 + -12 Combine like terms: -6 + -12 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| 8-(5-6x)=3(2+3x) | | (3x^2+x+1)-(2x^2-5x+6)= | | Cx+b=a | | a^2-a-63=0 | | 9x+19-22x=4-10x-4 | | (5y-1)=(-2y+4) | | x^2-6x-37=0 | | 0.7(7x+8)=2.7-(x-3) | | 5x+1(-5+2)=18-3 | | 4sqrt(x^2+2x)=4sqrt(3) | | 2x^2-3=x^2+6x | | 5y-7=-169 | | 7n-93=2n-13 | | 4g-3=1g+37 | | X^2+2mx+1=0 | | 23-5n=-3(3-n) | | 17=-7+3n | | x^3-2x=5 | | 9+7=n | | 2*(3x+4)=8*(2x-4) | | (3x^2+x+1)+(2x^2-3x-5)= | | 6z-3=z+7 | | (3y+7)=4 | | 8x+3=-9x-5 | | 6x+131=3x+184 | | 0.75y+9=0.5 | | 4c^3+4c^2-24=0 | | a^2+6a-63=0 | | p(t)=-2t^2+48t+30 | | 9x-3-4x=x+8+x | | 7(2x)-(10-3x)= | | p(t)=-2t+48t+30 |